2016
DOI: 10.5664/jcsm.6348
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Urinary Drug Screening in the Multiple Sleep Latency Test and Maintenance of Wakefulness Test

Abstract: Study Objectives: Multiple sleep latency testing (MSLT) and the maintenance of wakefulness test (MWT) are gold-standard objective tests of daytime sleepiness and alertness; however, there is marked variability in their interpretation and practice. This study aimed to determine the incidence of positive drug screens and their influence on MSLT, MWT, and polysomnographic variables. Methods: All patients attending Eastern Health Sleep Laboratory for MSLT or MWT over a 21-mo period were included in the study. Urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Consideration should be given to drug screening as part of the MSLT protocol, as several recreational and illicit drugs can affect both sleep and wake/alertness (i.e., barbiturates, benzodiazepines, cannabinoids, cocaine, methadone and opioids). [21][22][23] The available evidence suggests that up to 33% of adult patients undergoing MSLTs have a positive drug screen. Moreover, a significant number of patients (81% in one study), 23 had not reported use of the detected substance.…”
Section: Drugs and Drug Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration should be given to drug screening as part of the MSLT protocol, as several recreational and illicit drugs can affect both sleep and wake/alertness (i.e., barbiturates, benzodiazepines, cannabinoids, cocaine, methadone and opioids). [21][22][23] The available evidence suggests that up to 33% of adult patients undergoing MSLTs have a positive drug screen. Moreover, a significant number of patients (81% in one study), 23 had not reported use of the detected substance.…”
Section: Drugs and Drug Screeningmentioning
confidence: 99%
“…In a study by Anniss et al 2016, 6 out of 26 patients (16%) undergoing an MWT had a positive drug screen for either an amphetamine, cannabis, or benzodiazepine. 22 A variety of reasons motivated patients for their unreported drug use. If a drug screen is performed, the results should be clearly documented in the test report.…”
Section: Drugs and Drug Screeningmentioning
confidence: 99%
“…This work has several limitations. In addition to its retrospective design and small number of included NT1 patients, we must acknowledge that we did not perform urinary drug screening during MSLT/MWT and, hence, may have missed underhand consumption of psychostimulants, with the intention to avoid social/work-related restrictions or being banned from driving [36]. Second, although the employed radioimmunoassay kit for hypocretin-1 has a low inter-and intra-assay variability [19,37,38], its accuracy might be less reliable when CSF hypocretin levels are below 60 pg/ml, and the applied CSF hypocretin detection limit of 30 pg/ml might thus appear as too low.…”
Section: Discussionmentioning
confidence: 99%